Update breast cancer 2018 (Part 4): genomics, individualized medicine and immune therapies - in the middle of a new era : treatment strategies for advanced breast cancer = Update Mammakarzinom 2018 (Part 4) : Genomforschung, individualisierte Medizin und Immuntherapien - mitten in einer neuen Ära : Therapie des fortgeschrittenen Mammakarzinoms - Müller, Volkmar; Schütz, Florian; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2018)
New therapeutic developments aimed at treating women with advanced breast cancer currently focus both on identifying patients eligible for targeted therapeutic concepts and on the continuing development of immune therapies. The data on CDK4/6 inhibitors are now complete and consistent in this class of substances (palbociclib, ribociclib and abemaciclib). Further pathways under investigation are PI3K and AKT signalling pathways along with diverse approaches to their inhibition. Initial study results were also presented recently on both mechanisms of action. Insights into the PARP inhibitors, moreover, are increasing; studies in this respect are also examining in which population they can be used most effectively. This review offers a summary of the recent studies and an outline of the latest developments.